La casa de dios : the legacy of Filipino-Hispanic churches in the Philippines - Javellana, Rene. (Pasig City, Philippines : Ortigas Foundation, Inc., 2010)
This book is dedicated to Rafael Ortigas Jr. who, twelve years ago, initiated a project aimed at documenting and photographing all Spanish era churches in the Philippines.